IMPLEMENTASI PROGRAM MOBILE JKN DALAM MEMBERIKAN PELAYANAN PENGGUNA KIS DI KANTOR BPJS KESEHATAN KABUPATEN KARANGASEM - Puspa Widyasari, Sang Ayu Nyoman; Yasintha, Putu Nomy; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2019)
ABSTRACT The Mobile JKN application is an information technology-based application tofacilitate administrative services requirements through the application. One area that has implemented the Mobile JKN application is Karangasem Regency. The research uses the theory of Policy Implementation of Charles O. Jones, covering organization, interpretation, and application. This study uses descriptive qualitative methods. The results in this study make explanation that the implementation of the Mobile JKN program in Karangasem Regency not run quite well both in terms of organization and interpretation that has not gone well. Then the aspects of the application are quite good. Through the use of the Mobile JKN application, especially in Karangasem Regency, it is expected that it will make it easy for the public to take care of other administrative needs and can increase JKN users. Keywords: Public Services, Implementation, Mobile JKN